R&D Works of the Lvivska Politechnika National University - Pikh, Z. (Science and Innovation, 2024)
R&D works of Lviv Polytechnic National University researchers for the last five years, which outline the level of a complishments and the capacity of the University to work effectively for meeting the needs of market economy have been summarized. More information on R&D works of Lviv Polytechnic National University can be found at nauka.lp.edu.ua.